Pengaruh Pemberian Insentif Terhadap Kinerja Pegawai Penyuluh Pertanian Lapangan Pada Badan Ketahanan Pangan dan Penyuluhan Kabupaten Paser - Firdaus, Achmad Aprianor; Rimboko, Tegen Sayuk; Baiduri, Siti (ARBITRASE: Journal of Economics and Accounting, 2022)
The purpose of this study was to determine whether the provision of incentives affects the performance of field agricultural extension officers at the Food Security and Extension Agency, Paser Regency, East Kalimantan. From the results of research using the Simple Linear Regression method, it is known that the relationship between the provision of incentives and the performance of agricultural extension workers at the Food Security and Extension Agency of Paser Regency has a very strong influence, namely 81.2%. The magnitude of the variation in the contribution of incentives to improving the performance of field agricultural extension officers at the Paser Regency Food Security and Extension Agency was 66.0% while the remaining 34.0% was explained by other reasons not included in this study. The high percentage of other variables not included in this study, which is equal to 34.0%, which affects the performance of field agricultural extension officers at the Paser Regency Food Security and Extension Agency, can be caused by the increasing quality of its human resources, appropriate leadership management, appropriate work structure. as well as a comfortable and adequate work environment at the Food Security and Counseling Agency for Paser Regency. The benefits of this research can be used as input for those who need it, especially the Regional Government of Paser Regency and the Paser Regency Food Security and Extension Agency in an effort to improve the performance of field agricultural extension officers at the Paser Regency Food Security and Extension Agency to be used as material for evaluation and further thoughts, especially relating to the problem of incentives and the performance of field agricultural extension officers.